STAT4 single nucleotide gene polymorphisms and susceptibility to endometriosis-related infertility. (August 2016) - Zamani, Mohammad Reza; Salmaninejad, Arash; Akbari Asbagh, Firouzeh; Masoud, Ahmad; Rezaei, Nima
Abstract: Introduction: Endometriosis is a multifactorial benign gynecologic disorder, characterized by the ectopic growth of misplaced endometrial cells with complex genetic inheritance and changing of some immune based factors and also shares some autoimmune characteristics. However, it is not clear yet that how and when these immunological factors affect the initiation or progression of the disease. It has been shown that STAT4 is a predisposing gene in the development of some autoimmune diseases. Method: The study group comprised 114 patients with endometriosis and 92 sex-, age-, and ethnicity-matched healthy controls of Iranian ancestry. Four SNPs (rs7574865, rs7601754, rs7582694 and rs11889341) were genotyped using the MGB TaqMan. Results: A significant association in rs7582694 between C allele ( P  = 0.002, OR = 1.986, 95% CI: 1.262–3.126) and endometriosis was found in our study, while the G allele ( P  = 0.002, OR = 0.0503, 95% CI: 0.319–0.792) was significantly decreased in the patients population. The GC genotype ( P  = 0.004, OR = 2.234, 95% CI: 1.301–4.150) was also significantly overrepresented in the patients with endometriosis, while the frequency of GG genotype was significantly lower in the patient group, compared to the controls ( P  = 0.007, OR = 0.457, 95% CI: 0.256–0.813). Conclusions: Our results for the first time showed a significant association between rs7582694 alleles and genotypes and susceptibility to endometriosis in a population.